Evaluation of The Capacity of The Araya Pump House in Managing Flood of Kalibokor Channel Sisi Jl. Arief Rachman Hakim - Kelvin Gilang Romadhon; Adi Prawito; Farida Hardaningrum (NAROTAMA UNIVERSITY, Indonesia, 2022)
Kalibokor Channel is one of the primary channels in East Surabaya. This channel overflows during the rainy season. The inundation height that occurs is between 0-15 cm. Some of the flood-prone areas that the channel passes through are Manyar, Klampis, Gebang Putih, and JL. Arif Rahman Hakim. The Surabaya City Government built the araya pump house as a helper for the Kalibokor channel in order to reduce inundation on Jl. Arief Rachman Hakim and reduce the load on the Kalibokor pump house. The study was conducted by calculating the value of the planned rain and flood discharge, then analyzing the existing one and ending by recommending a new pump capacity design. The results of the analysis calculation obtained that the planned discharge entered the Kalibokor primary channel on the side of Jl. Arief Rachman Hakim is 18.56 m3/s while the existing capacity of the Kalibokor primary channel on the side of Jl. Arief Rachman Hakim can only accommodate a capacity of 16.6 m3/s.